Prophylactic use of rectal diclofenac in mitigating post endoscopic retrograde cholangiopancreatography pancreatitis risk and severity: low- vs high-dose efficacy and timing strategies— a meta-analysis - Maggie Liberty; Taufik Sungkar; Peggy Liberty (Medicinski glasnik, 2026)
Aim: Post endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most prevalent adverse event with significant morbidity following ERCP. Several guidelines have suggested the use of rectal diclofenac as a promising option to prevent PEP. Nonetheless, the recommended optimal dose and timing of administration remain unclear. The aim of this study was to evaluate the efficacy of different doses and timing of rectal diclofenac administration in preventing PEP. Methods: Literature search was conducted on 3 databases: PubMed/MEDLINE, Cochrane Library, and ScienceDirect. The included studies were evaluated for the method and reported data quality. Data were summarized and statistical analyses were performed with RevMan 5.4.1 software. Results: Thirteen eligible studies with a total of 8602 patients undergoing ERCP were included in this study. The result showed A significantly lower moderate-severe PEP prevalence in patients treated with rectal diclofenac compared to control (RR 0.67; 95% CI: 0.51-0.89; p=0.006) was found. High-dose rectal diclofenac significantly reduced the prevalence of moderate to severe PEP (RR 0.63; 95% CI: 0.450.89; p=0.008). Administering rectal diclofenac before procedure significantly lowered the prevalence of moderate to severe PEP (RR 0.66; 95% CI: 0.47-0.92; p=0.01). Adverse events related to ERCP procedure were comparable in both groups. No adverse event related to rectal diclofenac administration was reported across all studies. Conclusion: High-dose rectal diclofenac administered before ERCP procedure is effective in reducing the prevalence and severity of PEP, and is well tolerated with favourable safety profile.
Keywords: anti-inflammatory agents; non-steroids; pancreatitis; prevention; suppository